Preliminary Impact of IFRS 9 Implementation on The Lebanese Banking Sector - Darine Dib; Khalil Feghali (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - What is the impact of the new requirements of the expected credit loss (ECL) model on the Lebanese banking sector? Motivation - In spite the expansion of research in respect of International Financial Reporting Standard N0. 9 (IFRS 9) in the past few years, it is still in its infancy in developing countries. Meanwhile, empirical IFRS 9 studies for banks is yet considered little as compared to the theoretical aspect. Our study seeks to fill this gap by testing the impact of IFRS 9 on the Lebanese banking sector. This paper is the first comprehensive attempt to empirically assess the estimated impact of IFRS 9 as disclosed in the 2017 financial statements. Idea - This study examines if the increase in provision based on the new ECL is strongly positively related to the average credit losses for the last 5 years, the current provisions level for the loans portfolio, the portfolio of investment securities, and the portfolio of liquid assets. Data - The data were collected from 19 consolidated banks representing 91% of the total consolidated balance sheet of all Lebanese banks. Tools - To test study's hypotheses, we applied linear regression using SPSS. Findings - Two main results can be derived: First, we found that the impact of the new ECL model is not material to the banks' equity if we consider the excess regulatory provisions booked in anticipation of IFRS 9. Second, we found that the increase in provision based on the ECL model is strongly positively related to the portfolio of investments securities and negatively related to the historical credit loss ratio. Contribution - Empirical IFRS 9 studies for banks is yet considered little as compared to the theoretical aspect. Our study seeks to fill this gap by testing the impact of IFRS 9 on the Lebanese banking sector. The Lebanese banks are an interesting case because they play a key role in the Lebanese economy, acting as the main channel for capital inflows into the country and financing the largest part of the government's current account deficit.
Keywords: M41; 650; IFRS 9; Expected Credit Loss (ECL); Incurred Loss; Classification and measurement